MODERN NANOTECHNOLOGY-BASED DRUG DELIVERY SYSTEMS FOR INFLAMMATORY BOWEL DISEASE TREATMENT: A COMPREHENSIVE REVIEW - Konrad Zieliński,; Stanisław Jurkowski,; Mikołaj Zalewski,; Marianna Rudzińska,; Karolina Ganczar,; Michał Mazurek,; Karolina Buć,; Paweł Buć,; Jagoda Józefczyk,; Łukasz Krzystek, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Inflammatory bowel disease (IBD), principally comprising ulcerative colitis (UC) and Crohn’s disease (CD), represents a growing global health burden characterized by chronic, relapsing inflammation of the gastrointestinal tract. The pathogenesis is multifactorial, involving genetic susceptibility, gut microbiota dysbiosis, and a dysregulated immune response. Current pharmacological strategies, including aminosalicylates, corticosteroids, immunomodulators, and biologics, are effective but often limited by non-specific distribution, low local bioavailability due to rapid gastrointestinal clearance, and severe systemic adverse effects such as immunosuppression and hepatotoxicity. Consequently, there is an urgent clinical need for novel therapeutic approaches that can deliver drugs precisely to the inflamed mucosa while minimizing systemic exposure. Nanotechnology has emerged as a transformative strategy to address these challenges by enabling targeted, controlled, and efficient drug delivery.Objective: This narrative review aims to provide a comprehensive evaluation of the state-of-the-art nanotechnology-based drug delivery systems (DDSs) for IBD treatment. It critically analyzes specific targeting mechanisms-including passive accumulation via the epithelial enhanced permeability and retention (eEPR) effect, active receptor targeting, and stimuli-responsive release-and assesses the therapeutic efficacy of novel nanocarriers loading a wide range of bioactive agents.Materials and Methods: A structured narrative review was conducted based on an extensive analysis of scientific literature published between 2015 and 2025. The review included original in vitro and in vivo studies focusing on organic (polymeric, lipid, hydrogel), inorganic (metallic, silica), and biomimetic nanocarriers. Data extraction prioritized physicochemical properties (size, charge), specific targeting ligands (e.g., hyaluronic acid, mannose, folate), and the modulation of key inflammatory pathways (NF-κB, ROS scavenging, cytokine production).Results: The analysis revealed that nanoparticle-based systems significantly enhance drug accumulation in inflamed colonic tissues compared to free drugs. Passive targeting strategies leveraging the eEPR effect and charge-dependent mucoadhesion demonstrated improved retention times. Active targeting utilizing ligands for CD44 (hyaluronic acid), mannose receptors (CD206), and transferrin receptors facilitated superior cellular uptake by activated macrophages and epithelial cells. Innovative stimuli-responsive formulations, such as pH-sensitive liposomes, ROS-responsive nanozymes (e.g., cerium oxide, manganese-polyphenol), and enzyme-degradable polysaccharide carriers, provided precise release profiles triggered by the pathological microenvironment. These systems effectively restored the intestinal barrier, significantly reduced pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), and mitigated oxidative stress in murine colitis models. Furthermore, natural compounds like curcumin and resveratrol showed dramatically improved bioavailability and therapeutic potential when encapsulated in nanocarriers.Conclusion: Nanotechnology-based DDSs represent a promising frontier in IBD therapy, offering a paradigm shift from systemic immunosuppression to precision local treatment. By maximizing local drug concentration and minimizing off-target effects, these systems address the fundamental limitations of current pharmacotherapy. While preclinical results are highly encouraging, further research focusing on long-term safety, scalable manufacturing, and rigorous clinical validation is essential to translate these innovations into standard clinical practice.